PENGARUH LEVERAGE, RETURN ON ASSET, DAN SIZE TERHADAP TAX AVOIDANCE - Rika Valentia; Linda Santioso (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study is to know if there is an effect of leverage, institutional ownership, and profitability on tax avoidance in industrial sector companies listed on the Indonesia Stock Exchange for the period 2019-2021. This study uses 38 samples of industrial sector companies selected using a purposive sampling method. The data used was secondary data in the form of financial statements obtained from the IDX official website. The data is processed using multiple regression analysis with SPSS 25. The results of the study show that return on assets has a significant positive influence on tax avoidance, while leverage and size have no influence on tax avoidance. The implications of this study is to indicate that return on assets can affect companies in doing tax avoidance. Having a high profit will cause the company to do tax avoidance.